Problem solving ability of seventh grade students viewed from geometric thinking levels in search solve create share learning model - Wijayanti, Kristina; Nikmah, Aizzatun; Pujiastuti, Emi (Department of Mathematics, Universitas Negeri Semarang, 2018)
The purposes of this study was to know wether the student’s problem solving ability on SSCS and PBL learning models achive the mastery learning ; to compare the the student’s problem solving ability on SSCS and PBL learning models; to describe the problem solving ability student on SSCS learning model viewed from geometry thinking levels, and to know the quality of SSCS learning models. The method used was a mixed method. The population of this study was all students of SMP N 10 Semarang. The sample was chooseb by simple random sampling technique and class VII D as control class and VII G as experiment class.The quantitative data was analyzed by z-test to and the equivalence of two means. The qualitative data was analyzed through the validity test, data display, data reduction, and conclusion . Results indicated that either SSCS and PBL learning models have achieve the mastery learning of poblem solving ability test but there was no difference between students' problem solving abilitiy in the SSCS and PBL learning models. Students with PreRecognition and Visual can’t fully identify the properties of figure so it makes difficulty in solving problem. Students with Analysis level solve problem using the properties of certain figures.